Influence of geographical origin and ethnicity on mortality in patients on antiretroviral therapy in Canada, Europe, and the United States. - Antiretroviral Therapy Cohort Collaboration (ART-CC) (2013)
BACKGROUND: Our objective was to assess differences in all-cause mortality, as well as AIDS and non-AIDS death rates, among patients started on antiretroviral therapy (ART) according to their geographical origin and ethnicity/race in Europe, Canada, and the United States. METHODS: This was a collaboration of 19 cohort studies of human immunodeficiency virus-positive subjects who have initiated ART (ART Cohort Collaboration) between 1998 and 2009. Adjusted mortality hazard ratios (AHRs) were estimated using Cox regression. A competing risk framework was used to estimate adjusted subdistribution hazard ratios for AIDS and non-AIDS mortality. RESULTS: Of 46 648 European patients, 16.3% were from sub-Saharan Africa (SSA), 5.1% Caribbean and Latin America, 1.6% North Africa and Middle East, and 1.7% Asia/West; of 1371 patients from Canada, 14.9% were First Nations and 22.4% migrants, and of 7742 patients from North America, 55.5% were African American and 6.6% Hispanic. Migrants from SSA (AHR, 0.79; 95% confidence interval [CI], .68-.92) and Asia/West (AHR, 0.62; 95% CI, .41-.92) had lower mortality than Europeans; these differences appeared mainly attributable to lower non-AIDS mortality. Compared with white Canadians, mortality in Canadian First Nations people (AHR, 1.48; 95% CI, .96-2.29) was higher, both for AIDS and non-AIDS mortality rates. Among US patients, when compared with whites, African Americans had higher AIDS and non-AIDS mortality, and hazard ratios for all-cause mortality increased with time on ART. CONCLUSIONS: The lower mortality observed in migrants suggests "healthy migrant" effects, whereas the higher mortality in First Nations people and African Americans in North America suggests social inequality gaps.